Choline Chloride–Lactic Acid-Based NADES As an Extraction Medium in a Response Surface Methodology-Optimized Method for the Extraction of Phenolic Compounds from Hazelnut Skin - Chiara Fanali; Valeria Gallo; Susanna Della Posta; Laura Dugo; Leone Mazzeo; Marco Cocchi; Vincenzo Piemonte; Laura De Gara (Molecules, 2021)
Deep eutectic solvents (DESs) are promising green solvents for the extraction of compounds from food byproducts. Hazelnut (Corylus avellana L.) is one of the most commonly cultivated tree nuts worldwide. The skin represents one of the major byproducts of the hazelnut industry and accounts for 2.5% of the total hazelnut kernel weight. It is a rich source of phenolic compounds like flavan-3-ols, flavonols, dihydrochalcones, and phenolic acids. In this work, fifteen DESs based on choline chloride and betaine, with different compositions, were studied in order to test their phenolic compounds extraction efficiency through the determination of their total concentration via Folin–Ciocalteu assay. A qualitative analysis of extracted phenolic compounds was assessed by HPLC with UV and MS detection. Using the DES with the best extraction efficiency, a new ultrasound-assisted solid liquid extraction (UA-SLE) method was optimized though the response surface methodology (RSM), taking into account some extraction parameters. Efficient recovery of extracted phenolic compounds was achieved using a 35% water solution of choline chloride and lactic acid (molar ratio 1:2) as an extraction solvent, working at 80 °C and with a solid-to-solvent ratio of 1:25 gmL−1. The optimized conditions made it possible to recover 39% more phenolic compounds compared to a classic organic solvent.